Nitrogen interstitial defects in silicon. A quantum mechanical investigation of the structural, electronic and vibrational properties - Platonenko, Alexander; Gentile, Francesco Silvio; Maul, Jefferson; Pascale, Fabien; Kotomin, Eugene A.; Dovesi, Roberto (Elsevier B.V., 2019)
The vibrational features of eight interstitial nitrogen related defects in silicon have been investigated at the first principles quantum mechanical level by using a periodic supercell approach, a hybrid functionals, an all electron Gaussian type basis set and the Crystal code. The list includes defects that will be indicated as Ni (one N atom forming a bridge between two Si atoms), Ni-Ns (one interstitial and one substitutional N atom linked to the same Si atom), Ni-Ni (two Ni defects linked to the same couple of silicon atoms) and Ni-Sii-Ni (two Ni defects linked to the same interstitial silicon atom). Four 〈0 0 1〉 split interstitial (dumbbell) defects have also been considered, in which one lattice atom splits in two, and as a result the two interstitial atoms are three fold coordinated: they are two N (indicated as IN-N), one N and one Si (IN-Si), one N and one C (IC-N). For comparison, also the case with two Si atoms (ISi-Si) has been included. Four of these eight defects have unpaired electrons, and have been described through the UHF (Unrestricted Hartree-Fock like) computational scheme. The local defect geometry and the charge and spin density distributions have been analyzed. For the first time, intensities of IR and Raman spectra were calculated along with the frequencies, and this is crucial for the comparison of theoretical simulations with experiments. All these defects present very characteristic features in their IR spectrum, dominated by one or two very intense peaks. It has been possible to find a simulated counterpart to each one of the five peaks reported by Stein in 1985 (Applied Physics Letters, 47, 1339), and then to establish a correspondence between the microscopic structure of the defects and the IR intense peaks. The Raman spectra are in all cases dominated by the perfect silicon peak at about 530 cm−1, and are then not very useful for the characterization of the defects.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; Silicon; Point defects; Nitrogen defects; Infrared spectra; Raman spectra; CRYSTAL code